Association Between Type-specific HPV Infections and hTERT DNA Methylation in Patients with Invasive Cervical Cancer - MOLANO, MÓNICA (Cancer Genomics Proteomics, 2016)
Background: There exists limited information on the role of hTERT methylation, and its association with type-specific HPV infections in cervical cancer. Materials and Methods: Eighty-seven frozen samples were analyzed for type-specific HPV infection using a GP5(+)/GP6(+) PCR-RLB assay (RLB). hTERT DNA methylation analysis was performed using a newly developed PCR-RLB-hTERT. Results: Ninety-three percent of samples were HPV-positive and fifteen different types were detected. hTERT methylation analysis of region 1 revealed no methylation in 78.8% of the samples and partial methylation in 21.2%. In region two, 68.2% showed no methylation and 31.8% showed a pattern of partial methylation. An association between the alpha 9 and alpha 7 species with a pattern of no methylation of hTERT in the region 1 was established (p=0.02 and p=0.03, respectively). Conclusion: Differences in patterns of methylation of the hTERT core promoter [region 1 (nt -208 to -1) and region 2 (nt +1 to +104) relative to first ATG] are related to the HPV species present.